A priori theories for multimedia design, production and integration. (1st January 2000) - Stoyanov, Svetoslav; Kommers, Piet A.M.
This paper intends to explore the more fundamental theoretical notions underlying the design and configuration of educational multimedia systems. Though it starts its initial inventory with the more traditional theories, it also looks at the more alternative approaches based upon constructivism, adult learning and theories related to creativity and problem solving. Seen from the prospects in multimedia and hypermedia, vocational and adult training have the potential to place the learner in an active and more responsible position. At the same time, however, we see that the product rather than the process-oriented assessment paradigms will survive for several decades. This brings us to the conclusion that it is essentially the local actor (the teacher) and the managers of the local setting who should decide upon the balance between reproduction, understanding and constructionist effects for the student. The versatility of hypermedia programs seem to provide an excellent opportunity for teachers and training officers to decide in a more explicit way upon the instructional impact.